(untitled) (Journal of actual problems of jurisprudence, 2019)
This article displays the legal regulation of breeding achievements as оbjectof intellectual property, applied a new approach in the prism of three types of resources are displayed gaps and deficiencies of individual legislative acts of the Republic of Kazakhstan, made suggestions to improve the legislation in the field of agrarian business. Keywords: breeding achievements, intellectual property rights, agro-industry, agriculture, agricultural business.